Gastrosquise : estudo descritivo da evolução clínica na fase imediata pós-nascimento, com foco na indicação de terapia nutricional - Zem, Elisangela (2012)
Gastroschisis is a surgical neonatal emergency, with complex multidisciplinar treatment. Associated to corrective surgery, other factors influence the evolution, including nutritional therapy. Objective: Describe prevalence and outcome of cases gastroschisis in four hospitals in Cuiabá/MT between 2006 and 2010, involving factors that may influence the prognosis. Methods: Primary study, epidemiological, longitudinal, retrospective, descriptive in the neonatal intensive care unit of University Hospital Júlio Müller, Santa Rosa, Santa Casa de Misericórdia de Cuiabá and Santa Helena, admitted from January 2006 to December 2010. Results: From 2006 to 2010, 4171 newborns were admitted with resulted in a sample of 39 patients with gastroschisis (0.9%) in a total of 1053 days of hospitalization. The mean gestational age was 36.5 weeks, 56.4% were preterm newborn, 66.7% were born by cesarean delivery, 64.1% female, with a mean birth weight of 2.342 grams, 41% underwent surgical repair within the first hour of life. Over the 1053 days, was prescribed exclusive total parenteral nutrition in 58.9%, exclusive enteral nutrition in 14.1% enteral associated with parenteral nutrition therapy in 12.8% and absence of nutrition therapy in 14.2%. Conclusion: Establish and perform a proposal for exclusive enteral nutritional therapy or associated with parenteral therapy can contribute to an increase in survival rate of newborns suffering from gastroschisis.